Proceedinds of the twenty-fourth Standing Advisory Committee on Agricultural Credit - Reserve Bank of India (Bombay: Reserve Bank India, 1964)
This publication gives the note circulated in connection with the twenty-fourth meeting of the Standing Advisory Committee on Agricultural Credit and the proceedings.
gp. 25/01/2019
Loan
Keywords: Agricultural credit; Agricultural economics; Agricultural finance; India